Asymptotic expansions for quasi-stationary distributions of nonlinearly perturbed semi-Markov processes - Silvestrov, D.S. (Інститут математики НАН України, 2007)
Asymptotic expansions are given for quasi-stationary distributions of nonlinearly perturbed semi-Markov processes.